The expression of compassion in social work practice. Issue 1 (2nd January 2016) - Stickle, Marilyn
ABSTRACT: Compassion is a core value in social work. As an emerging topic in research, we are learning how to distinguish this higher-level mental faculty from empathy and seeing important implications for social work practice. Functional magnetic imagery technology is enabling researchers to study the neural responses of empathy and compassion as they are occurring. Empathy accompanies negative affect, activating a pain network, while compassion activates positive affect and regions associated with affiliation. Research focusing on compassion training demonstrates that compassion prevents empathic distress even with short periods of intervention. This article addresses the differences between empathy and compassion, compassion training and plasticity, and the implications for practitioner health, including spirituality. Compassionate presence is proposed as a way of practicing social work that encompasses both our humanitarian roots and current research.